2007
DOI: 10.1007/s00383-007-1876-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of the inguinal hernia during laparoscopic orchiopexy in palpable cryptoorchidism: preliminary report

Abstract: During the laparoscopic approach of undescended testis, an associated inguinal hernia is a frequent finding that must be treated at the same time. The objective of this presentation is to show the incidence and management of the inguinal hernia that were found during laparoscopic orchidopexy, reporting how the scar tissue will join the edges of the canal and the parietal peritoneum will grow above. Between January 1999 and December 2002, 31 patients with 33 palpable and nonpalpable undescended testes were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…1 The fundamentals of our theory are based on a previous publication in which we described the management of the inguinal hernia during laparoscopic orchidopexy. 2 During the pulling of the testicle into the abdominal cavity, we resected the associated hernia sac. Then, we descended the testicle through a new path, medial to the epigastric vessels.…”
Section: Introductionmentioning
confidence: 99%
“…1 The fundamentals of our theory are based on a previous publication in which we described the management of the inguinal hernia during laparoscopic orchidopexy. 2 During the pulling of the testicle into the abdominal cavity, we resected the associated hernia sac. Then, we descended the testicle through a new path, medial to the epigastric vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that 8 cases were associated with inguinal hernia, suggesting that the first orchiopexy failed because an inadequate operation was performed. In a recent study, Riquelme et al [14] reported that the resection of processus vaginalis as the most important step of pediatric hernia repair, even without closure of the internal ring during laparoscopic orchidopexy. The hernia space can be occupied by scar tissue, and the deperitonealized area will close completely over the internal inguinal ring [14].…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, Riquelme et al [14] reported that the resection of processus vaginalis as the most important step of pediatric hernia repair, even without closure of the internal ring during laparoscopic orchidopexy. The hernia space can be occupied by scar tissue, and the deperitonealized area will close completely over the internal inguinal ring [14]. We agree to this opinion based on our findings in previous cases of laparoscopic orchidopexy.…”
Section: Discussionmentioning
confidence: 98%
“…In the era of tension-free mesh repair, some surgeons perform hernia sac excision without ligation, whereas others adopt hernia sac reduction alone [4,5]. During laparoscopic hernioplasty, the associated hernia sac is left unsutured with no consequences [6,7].…”
Section: Introductionmentioning
confidence: 99%